Evaluation of Anticancer Effect of Ghost Pepper: A Bioinformatics Assessment - Mona Zamanian-Azodi; Mostafa Rezaei-Tavirani; Somayeh Esmaeili; Vahid Mansouri*; Babak Arjmand; Somayeh Jahani-Sherafat (Iranian Society of Pharmacognosy, 2021)
Background and objectives: Natural sources can be effective in treating diverse pathological conditions especially cancer. Molecular evaluations of pepper on renal cancer could provide further information about its anticancer property. Methods: To achieve a clear understanding of pepper effect on cancer cells, protein-protein interaction network analysis of differentially expressed proteins (DEPs) in human renal adenocarcinoma cells treated with ghost pepper were evaluated. Cytoscape V. 3.8.2 and its applications were applied to analyze the DEPs. Results: Centrality study showed CYCS and CAT as DEPs were the hub-bottlenecks that were essential for the network stability. Among the 10 introduced central proteins, eight individuals belonged to the added first neighbors from STRING database. The finding indicated that the main central proteins belonged to the first neighbors of the queried proteins and were involved in the anticancer activity. Conclusion: Analysis highlighted anticancer property of ghost pepper on the human renal adenocarcinoma cells and also antioxidant effect which was associated with catalase activity.